BJIHS continues to increase its H index on Google Scholar. - Coelho Paraguassu, Eber (Brazilian Journal of Implantology and Health Sciences, 2020)
Google Scholar is a Google search tool that allows you to search academic papers, school literature, university newspapers and various articles. Launched in November 2004, it started offering searches in Portuguese on January 10, 2006 [1]. Currently, the Google Scholar H index has become a CAPES evaluation criterion for classifying and ranking journals on the sucupira platform, through the Qualis note [2]. The BJIHS in just one year achieved the feat of having the H 6 index. This means that the newspaper has 6 articles with at least 6 citations within the Google Scholar database. We are very grateful to the authors of these articles who help to boost the BJIHS metrics and make the newspaper each edition more relevant within the scientific community.